Being a woman is already hard. Being a woman on the street is even harder": violence against homeless women in Brazil, Portugal, and France (PerCursos, 2025)
The article aims to discuss the situation of women experiencing socio-territorial vulnerability, with an emphasis on their exposure to the risk of street violence, taking into account aspects of intersectionality of race, gender, and class in the context of migratory journeys and displacement. It is assumed that capitalist accumulation, through dispossession, has produced a significant contingent of “undesirables” in the urban centers of strategic cities in both the Global North and South. To shed light on this process, secondary data from various national and international reports are used, along with empirical data collected through field research and digital ethnography, focusing on three countries: Brazil, Portugal, and France. The methodological approach followed is that of an expanded case study, combined with multi-sited ethnography. The findings reveal a convergence in the analyzed scenario, in which violence against women’s bodies remains an ever-present specter.
Keywords: immigrant women; socioterritorial vulnerabilities; intentionalities; violence; cities